EVALUASI KEMANDIRIAN PENGELOLAAN KEUANGAN KABUPATEN KONAWE - Hadisantoso, Erwin; Anto, La Ode; Djumatria, Wa Ode Sitti (JURNAL AKUNTANSI DAN KEUANGAN, 2018)
ABSTRACKThis study aims to determine the level of financial independence ratio of Konawe regency. Data collection techniques were conducted with interviews and documentation. The analytical method used is descriptive analysis method. The equipment used in this research is the Regional Independence Ratio and Growth Ratio.The results of this study indicate that Konawe District for the level of regional independence is instructive which means that the role of central government is more dominant than the independence of local governments (regions that are unable to carry out regional autonomy financially).Â Keywords: Regional Independence, Local Original Revenue, and Transfer Fund